Production and evaluation of edible macrofungi spawn adapted to the Amazonian biome - Reis Jr., Francisco Eduardo Monteiro dos; Seccadio, Lara Lima (Brazilian Journal of Production Engineering, 2026)
The cultivation of edible macrofungi represents a sustainable alternative for productive diversification in the Amazonian Biome. However, it demands technological adaptations compatible with the region’s environmental conditions, especially regarding the management of critical factors for mycelial development. This study aimed to develop spawn of Pleurotus ostreatus from primary isolates cultivated under Amazonian conditions. Corn was used as a substrate, comparing two preparation methods: Mineral-Buffered Boiling (MBB) and Immersion in Sugar Solution (ISS). Mycelial growth, contamination, and productive performance were analyzed. The MBB method yielded the best results, with lower contamination rates compared to ISS, and higher Biological Efficiency (11.51%) and Productivity Rate (8.00%), surpassing the commercial spawn. Nevertheless, the overall performance indicators (BE, PR, PP, and NB) were below average values reported in the literature. Despite this, the production of regionally adapted spawn shows promise, especially if environmental adjustments, such as improved humidity control, are implemented to enhance yield and support the consolidation of local fungiculture.
Keywords: Pleurotus ostreatus; regionally adapted spawn; fungiculture; Amazonian substrate